Two Amphioxus ApeC-Containing Proteins Bind to Microbes and Inhibit the TRAF6 Pathway - Li, Jin; Li, Yuhui; Fan, Zhaoyu; Chen, Shenghui; Yan, Xinyu; Yue, Zirui; Huang, Guangrui; Liu, Shumin; Zhang, Hao; Chen, Shangwu; Dong, Meiling; Xu, Anlong; et al. (Frontiers in Immunology, 2021)
The apextrin C-terminal (ApeC) domain is a class of newly discovered protein domains with an origin back to prokaryotes. Proteins containing ApeC (ACPs) have been found in various marine and aquatic invertebrates, but their functions and the underlying mechanisms are largely unknown. Early studies suggested that amphioxus ACP1 and ACP2 bind to bacterial cell walls and have a role in immunity. Here we identified another two amphioxus ACPs (ACP3 and ACP5), which belong to the same phylogenetic clade with ACP1/2, but show distinct expression patterns and sequence divergence (40-50% sequence identities). Both ACP3 and ACP5 were mainly expressed in the intestine and hepatic cecum, and could be up-regulated after bacterial challenge. Both prokaryotic-expressed recombinant ACP3 and ACP5 could bind with several species of bacteria and yeasts, showing agglutinating activity but no microbicidal activity. ELISA assays suggested that their ApeC domains could interact with peptidoglycan (PGN), but not with lipoteichoic acid (LTA), lipopolysaccharides (LPS) and zymosan A. Furthermore, they can only bind to Lys-type PGN from S. aureus, but not to DAP-type PGN from Bacillus subtilis and not to moieties of PGN such as MDPs, NAMs and NAGs. This recognition spectrum is different from that of ACP1/2. We also found that when expressed in mammalian cells, ACP3 could interact with TRAF6 via a conserved N-terminal non-ApeC region, which inhibited the ubiquitination of TRAF6 and hence suppressed downstream NF-κB activation. This work helped define a novel ACP subfamily with conserved structures and related yet diversified molecular functions. Its members have dual roles, with ApeC as a lectin and a conserved unknown region as a signal transduction regulator. These findings expand our understanding of the ACP functions and may guide future research on the role of ACPs in different animal clades.